Nutrients in Beverages - Grumezescu, Alexandru Mihai; Holban, Alina Maria (Science of beverages ;, 2019)
Nutrients in Beverages, Volume Twelve, in the Science of Beverages series, introduces the role of nutrients in beverages and provides details into the biological effects of beverage ingredients by presenting their nutritional properties and characterization. This scientific reference covers both the current state-of-the-art and future trends in the beverage industry, and is designed as a comprehensive guide to this area of research. Detailed research information is presented to not only help researchers and students understand the nature of the challenges associated with incorporating nutrients, but to also help strengthen the knowledge transfer between research institutions and industry.